PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SHIELD-ON SERVICE CABANG MALL BOTANI SQUARE KOTA BOGOR - Rizka Akbar, Irfan; Nirmala, Pebi (Journal of Research and Publication Innovation, 2023)
The purpose of this study was to determine the effect of motivation on employee performance, to determine the effect of the work environment on employee performance and to determine the effect of motivation and work environment on employee simultaneously on employee performance at PT. Shield On Service, Botanical Square Mall Branch, Bogor. The method used in this research is descriptive quantitative method. The sample used is the saturated sample technique, namely all employees of PT. Shield-On Service Botani Square Mall Bogor City Branch, totaling 89 employees. Data collection through questionnaires or questionnaires. The analytical technique used is instrument test, assumption test classical, multiple linear regression test, and hypothesis testong, namely t and f tests. The result’s of the partial hypothesis test/t test indicate that motivation has a positive and significant effect on employee performance with a value of t count > t table 6,094 > 1,98793. While the result’s of the the partial hypothesis test/t test indicate that the work environment variable has a positive and significant effect on employee performance with a value of t count > t table 3,172 > 1,98793. The result’s of simultaneous hypothesis f test indicate that motivation and work environment have a postive and significant influence on employee performance with a value of f count > f table 136,947 > 3,10 with a sig. value of 0,000b < 0,05.